SASTRA POPULER DI INDONESIA - Wahyuni Mumu (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Populer literature had been through a great development in Indonesia. Although it has significant differences compared to elite literature from its idea, theme, languange references and other literary aspects, but with its light and simple theme and package, popular literature gaining respect from literature lover. It’s interesting to see the impact of pop literature to Indonesian literary as a whole.